Textile-based electrode for electrocardiography monitoring - Syaidah Md Saleh; Nurul Ashikin Abdul-Kadir; Fauzan Khairi Che Harun; Dedy H. B. Wicaksono (Bulletin of Electrical Engineering and Informatics, 2020)
The increasing demand of smart garment for monitoring people’s health is due to comfortability, lightweight and flexibility properties of the textile could offer to the user. The textile-based electrocardiography (ECG) electrode is an alternative of commercially available silver/silver chloride (Ag/AgCl) electrode which could cause skin allergies to certain users and is not suitable for long-term monitoring electrode. In this paper, we report the performance of reduced graphene oxide (rGO) coated cotton fabric electrode to the effect of longevity and temperature. The ECG waveform and signal-to noise ratio (SNR) of the rGO-coated cotton electrodes were compared to that the performance of Ag/AgCl electrodes. The reliability characterization confirmed the rGO-coated cotton fabric conductance maintain at more than 80% even after 100 days of fabrication and the conductance measurement is increasing with respect to the temperature applied. The electrode shows lower in impedance value and the performance in acquiring ECG signal is comparable with the Ag/AgCl electrode. The vertical position rectangle-shaped electrode is recommended in measuring ECG signals. In conclusion, the rGO-coated cotton electrode with flexible dry-type electrode and excellent performance especially reliability and in capturing ECG signal had shown a promising result for further development.